LEAN MANUFACTURING ANALYSIS IN THE PRODUCTION PROCESS OF MAKING PAVING BLOCKS AT PT XYZ - Munang, Aswan; Mayaskuri , Afdian; Aliyah, Khikmatul (Lembaga Penelitian dan Pengabdian pada Masyarakat, Universitas Buana Perjuangan Karawang, 2025)
Manufacturing is an integral part of the production or material innovation process to increase the efficiency and effectiveness of company productivity. PT PT. XYZ is a company that utilizes plastic waste to be processed into paving block products. The problem is that the company does not reach the production target. PT PT. XYZ can improve performance in meeting market targets. The purpose of this research is to use the concept of lean manufacturing to identify activities that cause waste. The methods used are Value Stream Mapping (VSM) and Value Stream Analysis Tool (VALSAT). One of the analysis tools used is Process Activity Mapping (PAM) with a total weight of 139.9. In addition, this research identifies activities that can be categorized as value-added (VA), non-value-added (NVA), and non-value-added required (NNVA). The results obtained from this research can reduce cycle time from 517.53 minutes to 457.53 minutes. Evaluation of improvements using the 5W1H method describes the details of what problems occur in the production process starting from humans, machines, materials, methods, and the environment. Later the cause of the production process is described in 5W1H then by taking action for improvement.